Pengaruh Lingkungan Kerja, Motivasi Kerja, dan Disiplin Kerja Terhadap Kinerja Pegawai Dinas Komunikasi dan Informatika Kabupaten Karanganyar - Evi Puji Lestari; Sutarno (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Human resource management plays a crucial role in achieving organisational goals. This study aims to analyse the effect of work environment, work motivation, and work discipline on employee performance at the Karanganyar Regency Communication and Informatics Office. This study uses a survey approach to employees of the Karanganyar Regency Communication and Informatics Office by utilising quantitative data. Primary data was obtained through distributing questionnaires to 60 respondents selected from the population of all employees of the agency. The data analysis techniques applied include multiple linear regression tests, t tests, F tests, and coefficient of determination tests. Based on validity and reliability testing, all statement items related to work environment, work motivation, work discipline, and employee performance were confirmed valid with a significance value (p) less than 0.05, and reliable with a Cronbach's Alpha value exceeding 0.60.  The results of classical assumption testing indicate that all variables have met the criteria for multicollinearity, autocorrelation, heteroscedasticity, and normality tests, with normal data distribution. Linear regression analysis resulted in the equation: Y = 1.974 + 0.369 ????1 + 0.238 ????2 + 0.310 ????3 + e. The t test shows that the work environment variable (????1), work motivation (????2), and work discipline (????3) have a statistically significant effect on employee performance. The F test confirms that the regression model used in this study is appropriate. The coefficient of determination (R²) shows that the independent variables contribute 62.3% to the variability of the dependent variable, while the remaining 37.7% is influenced by other variables outside the model tested.